Influence of Milling Process on Efavirenz Solubility - Zaini, Erizal (J Pharm Bioallied Sci, 2017)
INTRODUCTION: The aim of this study was to investigate the influence of the milling process on the solubility of efavirenz. MATERIALS AND METHODS: Milling process was done using Nanomilling for 30, 60, and 180 min. Intact and milled efavirenz were characterized by powder X-ray diffraction, scanning electron microscopy (SEM), spectroscopy infrared (IR), differential scanning calorimetry (DSC), and solubility test. RESULTS: The X-ray diffractogram showed a decline on peak intensity of milled efavirenz compared to intact efavirenz. The SEM graph depicted the change from crystalline to amorphous habit after milling process. The IR spectrum showed there was no difference between intact and milled efavirenz. Thermal analysis which performed by DSC showed a reduction on endothermic peak after milling process which related to decreasing of crystallinity. Solubility test of intact and milled efavirenz was conducted in distilled water free CO(2) with 0.25% sodium lauryl sulfate media and measured using high-performance liquid chromatography method with acetonitrile: distilled water (80:20) as mobile phases. The solubility was significantly increased (P < 0.05) after milling processes, which the intact efavirenz was 27.12 ± 2.05, while the milled efavirenz for 30, 60, and 180 min were 75.53 ± 1.59, 82.34 ± 1.23, and 104.75 ± 0.96 μg/mL, respectively. CONCLUSIONS: Based on the results, the solubility of efavirenz improved after milling process.